Electrocatalytic water oxidation by a molecular cobalt complex through a high valent cobalt oxo intermediate - Das, Debasree; Pattanayak, Santanu; Singh, Kundan K.; Garai, Bikash; Sen Gupta, Sayam (Chemical Communications, 2016)
Biuret-modified tetraamidomacrocyclic cobalt complex [Co-III-bTAML]- is shown to catalyze electrochemical water oxidation at basic pH leading to the formation of O-2. Electrochemical and spectroscopic studies indicate a high valent cobalt oxo intermediate isoelectronic to Co-V(O) as the active oxidant. The kinetic isotope effect of 8.63 indicates an atom proton transfer mechanism.

Electrochemical formation of Fe-V (O) and mechanism of its reaction with water during O-O bond formation - Pattanayak, Santanu; Chowdhury, Debarati Roy; Garai, Bikash; Singh, Kundan K.; Paul, Amit; Dhar, Basab B.; Sen Gupta, Sayam (Chemistry-A European Journal, 2017)
A detailed electrochemical investigation of a series of iron complexes (biuret-modified tetraamido iron macrocycles FeIII-bTAML), including the first electrochemical generation of Fe-V(O), and demonstration of their efficacy as homogeneous catalysts for electrochemical water oxidation (WO) in aqueous medium are reported. Spectroelectrochemical and mass spectral studies indicated FeV(O) as the active oxidant, formed due to two redox transitions, which were assigned as Fe-IV(O)/Fe-III(OH2)and Fe-V(O)/Fe-IV(O). The spectral properties of both of these high-valent iron oxo species perfectly match those of their chemically synthesised versions, which were thoroughly characterised by several spectroscopic techniques. The O-O bond-formation step occurs by nucleophilic attack of H2O on FeV(O). A kinetic isotope effect of 3.2 indicates an atom-proton transfer (APT) mechanism. The reaction of chemically synthesised Fe-V(O) in CH3CN and water was directly probed by electrochemistry and was found to be first-order in water. The pK(a) value of the buffer base plays a critical role in the rate-determining step by increasing the reaction rate several-fold. The electronic effect on redox potential, WO rates, and onset overpotential was studied by employing a series of iron complexes. The catalytic activity was enhanced by the presence of electron-withdrawing groups on the bTAML framework. Changing the substituents from OMe to NO2 resulted in an eightfold increase in reaction rate, while the overpotential increased threefold.

Spectroscopic and reactivity comparisons of a pair of bTAML complexes with Fe-V=O and Fe-IV=O units - Pattanayak, Santanu; Jasniewsk, Andrew J.; Rana, Atanu; Draksharapu, Apparao; Singh, Kundan K.; Weitz, Andrew; Hendrich, Michael; Que, Lawrence, Jr.; Dey, Abhishek; Sen Gupta, Sayam (Inorganic Chemistry, 2017)
In this report we compare the geometric and electronic structures and reactivities of [Fe-V(O)](-) and [Fe-IV(O)](2-) species supported by the same ancillary nonheme biuret tetraamido macrocyclic ligand (bTAML). Resonance Raman studies show that the Fe-O vibration of the [Fe-IV(O)](2-) complex 2 is at 798 cm(-1), compared to 862 cm(-1) for the corresponding [Fe-V(O)](-) species 3, a 64 cm(-1) frequency difference reasonably reproduced by density functional theory calculations. These values are, respectively, the lowest and the highest frequencies observed thus far for nonheme high-valent Fe-O complexes. Extended X-ray absorption fine structure analysis of 3 reveals an Fe-O bond length of 1.59 angstrom, which is 0.05 angstrom shorter than that found in complex 2. The redox potentials of 2 and 3 are 0.44 V (measured at pH 12) and 1.19 V (measured at pH 7) versus normal hydrogen electrode, respectively, corresponding to the [Fe-IV(O)](2-)/[Fe-III(OH)](2-) and [Fe-V(O)](-)/[Fe-IV(O)](2-) couples. Consistent with its higher potential (even after correcting for the pH difference), 3 oxidizes benzyl alcohol at pH 7 with a second-order rate constant that is 2500-fold bigger than that for 2 at pH 12. Furthermore, 2 exhibits a classical kinteic isotope effect (KIE) of 3 in the oxidation of benzyl alcohol to benzaldehyde versus a nonclassical KIE of 12 for 3, emphasizing the reactivity differences between 2 and 3.

What drives the H-abstraction reaction in bio-mimetic oxoiron-bTAML complexes? A computational investigation - Mukherjee, Anagh (Physical Chemistry and Chemical Physics, 2018)
Monomeric iron-oxo units have been confirmed as intermediates involved in the C–H bond activation in various metallo-enzymes. Biomimetic oxoiron complexes of the biuret modified tetra-amido macrocyclic ligand (bTAML) have been demonstrated to oxidize a wide variety of unactivated C–H bonds. In the current work, density functional theory (DFT) has been employed to investigate the hydrogen abstraction (HAT) reactivity differences across a series of bTAML complexes. The cause for the differences in the HAT energy barriers has been found to be the relative changes in the energy of the frontier molecular orbitals (FMOs) induced by electronic perturbation.